STUDI KUALITATIF: PENGALAMAN ADAPTASI IBU HAMIL - Ratu Kusuma (Jurnal Akademika Baiturrahim Jambi, 2018)
Pregnant women will experience various changes during pregnancy such as physiological, psychological and social changes. The inability of mothers to adapt to these changes not only causes disruption during pregnancy, but also it can continue in the postpartum period, one of them is postpartum depression. This study aimed to explore the experiences of adaptation of pregnant women, includes perceived stimulus, coping used and adaptation behavior responses indicated by pregnant women. This is a qualitative research by using phenomenology approach at the public health center in Kabupaten Kampar, Riau. Participants in this study were 9 pregnant women, aged 24-38 years, Junior High School-Graduate Education, gestational age 5-29 weeks,  the number of children living 1-5 people, children rank age 9  months to 3.5 years, work varies, namely housewives, corporate employees, honors teachers and traders. The collecting data of indepth interview method and observations, recorded using a tape recorder, and then took notes the results of these observations. Based on the data obtained that 7 themes namely 1) Depressive symptoms in pregnant women; 2) Complaints of pregnant women related to nutritional intake; 3) Health problems of pregnant women; 4) Family problem 5) family financial problems 6) coping used by pregnant women 7) adaptive behavioral responses of pregnant women. There were various stimuli felt by pregnant women, namely physiological, psychological and social stimuli. Coping used by pregnant women in reducing the perceived stimulus that was adaptive and not adaptive coping, while the adaptation behavior response indicated by pregnant women was response to physiological adaptation behavior, self-concept, role function and interdependent. Therefore, it is necessary to develop models in the form of providing education to couples of pregnant women in helping mothers adapt, in an effort to prevent the occurrence of postpartum depression.